SINERGI KAMPUS BERDAMPAK TERHADAP SISTEM PENGELOLAAN DAN EKOSISTEM PESISIR UNTUK OPTIMALISASI TOURISM KAWASAN WISATA TANJUNG LUAR MENUJU PARIWISATA BERKELANJUTAN - Furkan, Lalu Muhammad; Putra, Muhamad Gilang Rahardi; Jurnal Wicara; Nazira, Arni; Rahmawati, Yuliana; Marsha, Audy Thaliqa; Wulandari, Sri Hikmah; Antu, Thio Alqolby; Putra, I Gusti Bagus Widiadnyana Windra; Putri, Adinda Melisa; Febiola, Nela; Midrawati, Laela (Universitas Mataram, 2025)
Community Service Program (KKN) is an intracurricular activity that integrates the Three Pillars of Higher Education with community learning experiences. The University of Mataram's KKN-PMD program, implemented in Tanjung Luar Village, Keruak District, East Lombok Regency, focused on developing tourism potential and addressing social, educational, and environmental issues. Through surveys and discussions with the community, students designed key programs, including the construction of a tourist data center, the provision of a waste incinerator, and the development of a promotional website for the tourism village. Additionally, other activities included outreach on the dangers of online loans, school instruction, Quran reading training, fish bone meal production, mangrove planting, and English language instruction for fishermen. The results of these activities demonstrated improvements in tourism support facilities and strengthened social relations between students and the community. This program demonstrates that KKN can be an effective tool in supporting community-based tourism management and sustainable village development